(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2022)
A diverse fish paleofauna occurs in the upper Campanian portion of the Rybushka Formation exposed near Saratov city in the Saratov Oblast, Russia. Twenty taxa have been identified, including two holocephalans (Ischyodus bifurcatus and Amylodon karamysh), twelve elasmobranchs (Synechodus sp., Cederstroemia sp., Cretalamna cf. C. borealis, C. cf. C. sarcoportheta, Archaeolamna kopingensis, Eostriatolamia segedini, E. venusta, Pseudocorax laevis, Squalicorax kaupi, Squalicorax morphotype 1, Squalidae indet., and Squatirhina sp.), and six teleosts (Pachyrhizodus sp., Saurocephalus lanciformis, Paralbula casei, Enchodus cf. E. dirus, E. cf. E. gladiolus, and E. petrosus). Many of these taxa are new to the Campanian fish record of Russia, and the assemblage demonstrates that there is significant taxonomic overlap between the Rybushka Formation paleofauna and that of North America.